2002
DOI: 10.1083/jcb.200204076
|View full text |Cite
|
Sign up to set email alerts
|

α1-Syntrophin–deficient skeletal muscle exhibits hypertrophy and aberrant formation of neuromuscular junctions during regeneration

Abstract: α1-Syntrophin is a member of the family of dystrophin-associated proteins; it has been shown to recruit neuronal nitric oxide synthase and the water channel aquaporin-4 to the sarcolemma by its PSD-95/SAP-90, Discs-large, ZO-1 homologous domain. To examine the role of α1-syntrophin in muscle regeneration, we injected cardiotoxin into the tibialis anterior muscles of α1-syntrophin–null (α1syn−/−) mice. After the treatment, α1syn−/− muscles displayed remarkable hypertrophy and extensive fiber splitting compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 56 publications
3
55
0
1
Order By: Relevance
“…Western blotting was performed as previously described (Hosaka et al, 2002). In brief, 20 lg of muscle proteins were separated on 7.5% SDS-PAGE gels and transferred to a PVDF membrane (Millipore, Bedford, MA).…”
Section: Western Blottingmentioning
confidence: 99%
“…Western blotting was performed as previously described (Hosaka et al, 2002). In brief, 20 lg of muscle proteins were separated on 7.5% SDS-PAGE gels and transferred to a PVDF membrane (Millipore, Bedford, MA).…”
Section: Western Blottingmentioning
confidence: 99%
“…eNOS-null muscle revealed atrophy during tail suspension similar to that seen in wildtype muscle (Figure 2, A and B), indicating that eNOS is not essential for atrophy signaling. We previously reported that disruption of the α1-syntrophin gene resulted in dislocation of nNOS from the sarcolemma to the cytoplasm without dystrophic phenotypes (25,26). Suspension of α1-syntrophin-null mice induced severe muscle atrophy as it did in wild-type muscle ( Figure 2, A and B).…”
Section: Nnos Disappears From the Sarcolemma During Tail Suspensionmentioning
confidence: 99%
“…After a cardiotoxin treatment, muscles from mice lacking a1-syntrophin, another member of the DAPC, displayed remarkable hypertrophy and extensive fibre splitting compared with wild-type regenerating muscles, although the untreated muscles of the mutant mice showed no gross histological change (Hosaka et al 2002). The lack of a1-syntrophin also might be responsible in part for reduced force generation during regeneration of dystrophin-deficient muscle (Hosaka et al 2002). In another way, Amali et al (2008) reported that overexpression of a new form of myostatin, Mstn2, a member of the TGF-beta superfamily reduces the expression of dystrophin-associated protein complex (DAPC) which leads to muscle dystrophy in zebrafish.…”
Section: Discussionmentioning
confidence: 98%
“…Dystrophin and proteins of the dystrophin-associated protein complex (DAPC), such as dystroglycan, and sarcoglycan are important for muscle integrity (Grady et al 1997;Collins and Morgan 2003). After a cardiotoxin treatment, muscles from mice lacking a1-syntrophin, another member of the DAPC, displayed remarkable hypertrophy and extensive fibre splitting compared with wild-type regenerating muscles, although the untreated muscles of the mutant mice showed no gross histological change (Hosaka et al 2002). The lack of a1-syntrophin also might be responsible in part for reduced force generation during regeneration of dystrophin-deficient muscle (Hosaka et al 2002).…”
Section: Discussionmentioning
confidence: 99%